The impact of intelligent devices utilization on household medical expenditure of older adults in China - Jingjing Wang; Lianjie Wang (Scientific Reports)
Abstract With the rapid development of artificial intelligence, there is an increasing utilization of intelligent devices by older adults. The relationship between the utilization of intelligent devices and household medical expenditure has garnered widespread attention in academic circles. This paper employs data from the 2020 China Longitudinal Aging Social Survey (CLASS) to investigate the impact of intelligent device utilization by 9,718 older adults on household medical consumption. The research findings indicate that the utilization of intelligent devices significantly reduces household medical expenditure, and this conclusion remains valid after placebo tests and endogeneity treatments. From the perspective of heterogeneity, the impact of intelligent device utilization on household medical expenditure is more pronounced among higher age, those living with family, residents of eastern and western regions, and areas with high digital coverage. Quantile regression results reveal a “inverted U-shaped” trend in the impact of intelligent device utilization on household medical expenditure, with an initial increase followed by a decrease. Mechanism analysis suggests that intelligent device utilization reduces household medical expenditure by improving the health behaviors and decreasing the demand for medical services. Based on these findings, this paper argues that enterprises and research institutions should continue to develop intelligent devices tailored to the characteristics of older adults. The government should provide financial subsidies to purchase intelligent devices for older adults. By fully enhancing the utilization of intelligent devices in elderly health management, we can together provide a reference for controlling the excessive growth of medical expenses.